The Costly and Demanding: Exploring Solution-Based Othering of “Non-European Immigrants” in Norwegian Policy Recommendations - Andreasen, Søren Mosgaard (Nordlit, 2019)
This article examines the Norwegian scholarly report titled NOU 2017:2—Integration and Trust: Long-Term Consequences of High Immigration (English translation; chapter 1.1) to unpack how ‘non-European immigrants’ are constructed as an economic and social challenge for the welfare state. Principles from discourse theory (DT) and the conceptual framework of othering are applied to discuss how the designation of this category of people as objects of qualification/integration may serve to reify racialized relations of inferiorized difference between white Norwegian majorities and societal newcomers from the Global South. The author tracks this dynamic to a discourse in which the relationship between the Norwegian state and immigrants from countries outside of Europe is organized as a binary opposition between a vulnerable self and an overwhelming, inherently faceless ‘other’. It is suggested that the othering enabled in the NOU (Norges Offentlige Utredninger) report can be viewed as a specific production of monstrosity: a horror-vision of a failing, unintegrated welfare state that needs safeguarding against abnormal, ‘huge waves’ of immigrants from ‘further south’. The argument is finally presented that the report’s vision of integration, by being coded with the logic of presenting a necessary response to an existential threat to welfare state structures, engenders a precarious form of social distancing that is theorized as solution-based othering.